Gut-brain axis in post-traumatic stress disorder: microbial - mediated mechanisms and new therapeutic approaches - A narrative review - Pan, Jiayue; Lin, Shuairong; Qian, Qiuling; Fu, Shanni; Liu, Xiaoliu (Frontiers in Pharmacology, 2025)
Post-traumatic stress disorder (PTSD) is a severe mental disorder that occurs after experiencing or witnessing a traumatic event. Not only does this disorder severely impair the quality of life and emotional wellbeing of patients, but in recent years the global rate of PTSD diagnoses has increased to 1.5–2 times, and the prevalence of PTSD associated with COVID-19 events in particular has surged to 10%–25%, underscoring the urgency of developing effective treatments. The lifetime prevalence of PTSD in the general population is estimated to be approximately 3.9%, while in high-risk populations, such as war veterans, it can be as high as 30%. As a key pathway connecting the central nervous system to peripheral organs, the gut-brain axis has received increasing attention for its role in PTSD. Although the gut-brain axis has been shown to be associated with several psychiatric disorders, especially depression, its specific role in PTSD remains undercharacterized. Existing studies suggest that specific strains of Lactobacillus (e.g., Lactobacillus reuteri) may alleviate inflammatory responses and improve PTSD-like behaviors by down-regulating the expression of pro-inflammatory factors (IL-6 and TNF-α). In this study, we used a narrative review approach to sort out the research progress of gut microbiota alteration in PTSD, and compared the characteristics of changes in specific microbial taxa (e.g., Bacteroides, Lactobacillus, etc.), the index of microbiota diversity (α/β diversity), and the levels of inflammatory markers (e.g., IL-6, TNF-α) between the animal model and the human patients, respectively, in order to We further explored the potential pathogenic mechanisms mediated by microorganisms, such as influencing the vagal pathway, hypothalamic-pituitary-adrenal (HPA) axis function, immune system and other processes involved in the pathology of PTSD, and summarized the intervention strategies targeting gut microecology, such as probiotic supplementation, dietary interventions and fecal bacteria transplantation.